NILAI-NILAI AMERICAN CREED STUDI MENGENAI SISTEM KEPERCAYAAN BANGSA MAJEMUK AMERIKA - Ariesani Hermawanto; Melaty Anggraini (Jurnal Paradigma, 2020)
United States is a new nation and its inhabitants plural because the citizens mostly descendants of immigrants from around the world and specifictly from Europe which is made various culture that has own. The various cultures made American citizen created the new value of culture that’s had they own featured. Culture Value’s they used for facing various issues and becomes guidance for every single decision. The Culture Value’s is known American Creed, which is transformed become idea politic. Liberalism is a central tenet of American citizens’ ideology about independence and individual rights. The values of capitalism, democracy, individualism, and egalitarianism in the important position. The Americans have a shared belief known as the American Creed. This paper aims to discuss the values of the American people which are part of the American creed. The results of this paper show that the values of the national beliefs have significant role for the unity of America. Political ideals that unite the American people can coexist with diversity in social values and cultural.